GDF-15 (Growth Differentiation Factor 15) Is Associated With Lack of Ventricular Recovery and Mortality After Transcatheter Aortic Valve Replacement. (December 2017) - Kim, Juyong Brian; Kobayashi, Yukari; Moneghetti, Kegan J.; Brenner, Daniel A.; O'Malley, Ryan; Schnittger, Ingela; Wu, Joseph C.; Murtagh, Gillian; Beshiri, Agim; Fischbein, Michael; Miller, D. Craig; Liang, David; et al.
N/A: Background—: Recent data suggest that circulating biomarkers may predict outcome in patients undergoing transcatheter aortic valve replacement (TAVR). We examined the association between inflammatory, myocardial, and renal biomarkers and their role in ventricular recovery and outcome after TAVR. Methods and Results—: A total of 112 subjects undergoing TAVR were included in the prospective registry. Plasma levels of B-type natriuretic peptide, hs-TnI (high-sensitivity troponin I), CRP (C-reactive protein), GDF-15 (growth differentiation factor 15), GAL-3 (galectin-3), and Cys-C (cystatin-C) were assessed before TAVR and in 100 sex-matched healthy controls. Among echocardiographic parameters, we measured global longitudinal strain, indexed left ventricular mass, and indexed left atrial volume. The TAVR group included 59% male, with an average age of 84 years, and 1-year mortality of 18%. Among biomarkers, we found GDF-15 and CRP to be strongly associated with all-cause mortality ( P <0.001). Inclusion of GDF-15 and CRP to the Society of Thoracic Surgeons score significantly improved C index (0.65–0.79; P <0.05) and provided a category-free net reclassification improvement of 106% at 2 years ( P =0.01). Among survivors, functional recovery in global longitudinal strain (>15% improvement) and indexed left ventricular mass (>20% decrease) at 1 year occurred in 48% and 22%, respectively. On multivariate logistic regression, lower baseline GDF-15 was associated with improved global longitudinal strain at 1 year (hazard ratio=0.29; P <0.001). Furthermore, improvement in global longitudinal strain at 1 month correlated with lower overall mortality (hazard ratio=0.45; P =0.03). Conclusions—: Elevated GDF-15 correlates with lack of reverse remodeling and increased mortality after TAVR and improves risk prediction of mortality when added to the Society of Thoracic Surgeons score. Abstract : Supplemental Digital Content is available in the text.